Estimation of inbreeding depression on female fertility in the Finnish Ayrshire population - Martikainen, K.; Tyrisevä, Anna-Maria; Matilainen, Kaarina; Poso, J.; Uimari, P. (Wiley, 2017)
Single nucleotide polymorphism (SNP) data enable the estimation of inbreeding at the genome level. In this study, we estimated inbreeding levels for 19,075 Finnish Ayrshire cows genotyped with a low-density SNP panel (8K). The genotypes were imputed to 50K density, and after quality control, 39,144 SNPs remained for the analysis. Inbreeding coefficients were estimated for each animal based on the percentage of homozygous SNPs (FPH), runs of homozygosity (FROH) and pedigree (FPED). Phenotypic records were available for 13,712 animals including non-return rate (NRR), number of inseminations (AIS) and interval from first to last insemination (IFL) for heifers and up to three parities for cows, as well as interval from calving to first insemination (ICF) for cows. Average FPED was 0.02, FROH 0.06 and FPH 0.63. A correlation of 0.71 was found between FPED and FROH, 0.66 between FPED and FPH and 0.94 between FROH and FPH. Pedigree-based inbreeding coefficients did not show inbreeding depression in any of the traits. However, when FROH or FPH was used as a covariate, significant inbreeding depression was observed; a 10% increase in FROH was associated with 5 days longer IFL0 and IFL1, 2 weeks longer IFL3 and 3 days longer ICF2 compared to non-inbred cows.
Keywords: inbreeding depression; nautakarja; sukusiitos; hedelmällisyys; cattle; inbreeding; fertility; SNP